University freshmen's excessive smartphone use and psychological safety during the COVID-19 pandemic - Yang, Qingsong; Shi, Mengxi; Zeng, Lianping; Xu, Ping (Frontiers in Psychiatry, 2022)
Although excessive smartphone use has been confirmed as being associated with specific representations of mental health (e. g., anxiety, depression, wellbeing, etc.) throughout the COVID-19 pandemic, the relationship between excessive smartphone use and cognitive representations of mental health (i.e., psychological safety) is not yet fully understood. This study aimed to identify the association between excessive smartphone use and psychological safety among university freshmen during the COVID-19 pandemic; in addition, we examined the mediation effects of hardiness and interpersonal distress in this relationship. In this study, 1,224 university freshmen were selected at random from several universities in Guizhou Province of China. The Psychological Safety Scale was used to evaluate the mental health of university freshmen; the Mobile Phone Dependence Scale was used to evaluate excessive smartphone use; the Hardiness Questionnaire was used to evaluate hardiness; and the Interpersonal Relation Synthetic Diagnose Test was used to evaluate interpersonal distress. The findings showed that: (1) the greater the degree of excessive smartphone use, the more serious respondents' interpersonal distress and the lower their hardiness; (2) excessive smartphone use was not only directly related to the psychological safety of university freshmen but also indirectly related to their psychological safety through the independent mediation of hardiness and interpersonal distress, as well as through the chain mediation of hardiness and interpersonal distress. In general, excessive smartphone use in university freshmen could lead to a decline in their psychological safety. Also, hardiness and interpersonal distress play a complex role in this relationship. During the COVID-19 pandemic, interventions on the mental health of college freshmen should not only provide guidance on how to use their smartphone responsibly but also to provide them with support and guidance for the enhancement of their hardiness and improvement of their interpersonal relationships.